Peran kepuasan pasien dalam memediasi pengaruh profesionalisme pemberi pelayanan terhadap niat berkunjung kembali pada RS PKU Muhammadiyah Surakarta - Kurniawati, Novarina; Kuswati, Rini; Ichsan, Burhannudin (Journal of Management and Digital Business, 2025)
This study aims to determine and examine the relationship between patient satisfaction, professionalism of service providers, and intention to revisit the hospital so that it can be input for hospitals to improve the quality of their services and build good relationships with patients. This study is a quantitative study using a survey method. Sampling was carried out using the Purposive Sampling Technique. The population was patients and their families at PKU Muhammadiyah Surakarta Hospital. The study was conducted on 153 respondents. Data collection was done using a questionnaire on Google Forms, and regression analysis was used as an analysis technique. The findings show that the professionalism of service providers has a positive effect on patient satisfaction, patient satisfaction has a positive effect on intention to revisit, and the professionalism of service providers has a positive effect on intention to revisit. In addition, the professionalism of service providers through patient satisfaction has a significant effect on the intention to revisit.